How does exercise regulate the physiological responses of post traumatic stress disorder? the crosstalk between oxidative stress and the hypothalamic-pituitary-adrenal axis - Zhang, Tianyu; Kong, Jianda (Frontiers in Physiology, 2025)
Post traumatic stress disorder (PTSD) is a severe psychological disorder cautilized by extreme traumatic events, typically accompanied by physiological mechanisms, such as oxidative stress and dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis. Our review explores how exercise boosts the physiological response of PTSD patients by regulating oxidative stress and HPA axis function, and delves into the potential mechanisms and application prospects of exercise in PTSD treatment. By a review of existing literature, we mainly discussed the effects of various types of exercise, like aerobic exercise, strength training, and high-intensity interval training (HIIT), on oxidative stress markers and HPA axis function, and evaluated the efficacy and mechanism of exercise intervention in the treatment of post traumatic stress disorder. Specifically, regular exercise can enhance the antioxidant defense system, reduce levels of reactive oxygen species (ROS), restore HPA axis function, and thereby alleviate the psychological and physiological symptoms of post-traumatic stress disorder. Different types of exercise have varying influences on the regulation of oxidative stress and cortisol secretion patterns. As a multidimensional therapeutic approach, exercise can provide comprehensive therapeutic advantages by enhancing neural plasticity, promoting immune function, and improving psychological resilience. In addition, the combination of exercise with conventional treatment strategies, such as cognitive-behavioral therapy and medication has apparently optimized treatment outcomes.